Practical course supporting English language learning for the 1st year students, semester 2 (все направления подготовки) электронный курс - Кудряшова, А. В. лингвист старший преподаватель Томского политехнического университета 1979- (TPU Moodle, 2020)
The course is intended for developing listening, reading, writing and speaking skills, revising grammar material and increasing vocabulary on the topics concerned. The course is developed for learning English for General Purposes by the first year students of TPU, 2nd semester. The required level of English is A1-B1. The course is intended for 18 hours.